The Framework Convention on Tobacco Control in Slovakia and in Finland: one law, two different practices? - Barbara Pavlikova; Jitse P. van Dijk (BMC, 2020)
Abstract Background The Framework Convention on Tobacco Control (FCTC) was ratified in 2004 in Slovakia and in 2005 in Finland. The aim of this study was to compare the implementation of the FCTC in the national laws and policies regarding smoking in Finland and Slovakia. Methods In this case study the following areas are compared: the legal framework; the monitoring system and health promotion; treatment; and policies aimed at reducing tobacco consumption. We report on these in this order after a short historical introduction. Results The legal frameworks are similar in Slovakia and in Finland. Finland far exceeds the minimum legal requirements. Slovakian regulations reflect the FCTC requirements; however, social tolerance is very high. In Finland the monitoring system and health promotion are aimed more at tobacco consumption. Slovakia does not follow the surveillance plans recommended by WHO so strictly; often there are no current data available. No additional documents regarding the FCTC have been adopted in Slovakia. The financial contribution to treatment is very low. Slovakian tobacco control policy is more focused on repression than on prevention, in contrast to Finland. Smoking bans meet European standards. Excise duties rise regularly in both countries. Conclusion Implementation of the FCTC is at different levels in the compared countries. Finland has a clear plan for achieving the goal of a smoking-free country. Slovakia meets only the minimum standard required for fulfillment of its international obligations. Its policy should become more transparent by making more up-to-date data available.